Rolled vs. finely ground pelleted sorghum grain in cattle rations - Richardson, D.; Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
In previous tests where grain intake was held at the same level, finely ground pelleted sorghum grain has produced larger and more efficient grain than rolled sorghum grain. This test was conducted to study the value of the two methods of grain preparation when the rest of the ration was held at a constant level and the grain fed according to the amount the animals would consume
Keywords: Beef; Rolled vs. finely ground pelleted sorghum grian